Improving efficiency in green tea production time using lean manufacturing approach with value stream mapping: A case study at PT Candi Loka [Perbaikan efisiensi waktu produksi teh hijau menggunakan pendekatan produksi ramping dengan value stream mapping: Studi kasus di PT Candi Loka] - Purnomo, Bambang Herry; Suryaningrat, Ida Bagus; Rachman, Ilham Aulia (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
Green tea production activities at PT Candi Loka indicated a time-consuming, which caused process efficiency to be less than optimal. Process efficiency improvements must be made to increase company competitiveness and consumer satisfaction. This research aimed to analyze the efficiency of green tea production time at PT Candi Loka by identifying the processing time required in each production activity, including the time consumption and formulating recommendations for improvement using a lean manufacturing approach using the VSM (Value Stream Mapping) method. There were 30 activities in 6 processes consisting of receiving raw materials, withering, rolling, drying, and packaging. Identification of value streams using the PAM (Process Activity Mapping) tool produced 9 Value added (VA) activities, 19 Necessary but Non-Value Added (NNVA) activities, and 2 Non-Value Added (NVA) activities in the form of delays in the withering and drying processes. In the current state map analysis, the production lead time value was 315.286 seconds. Recommended improvements to eliminate delays in the withering process were to set up the rotary panner machine earlier and increase the number of supervisors, while to eliminate delays in the drying process were to implement a piece rate system. Increasing efficiency was also carried out by improving NNVA activities by adding weighbridge facilities and using a conveyor system. The future state map proposed by implementing recommended improvements resulted in an increase in production time efficiency to 222.356 seconds and an increase in the process cycle efficiency value from 58.95% to 84.85%.